Autophagy and NLRP3 inflammasome crosstalk in neuroinflammation in aged bovine brains. Issue 6 (5th January 2020) - De Biase, Davide; Piegari, Giuseppe; Prisco, Francesco; Cimmino, Ilaria; Pirozzi, Claudio; Mattace Raso, Giuseppina; Oriente, Francesco; Grieco, Edoardo; Papparella, Serenella; Paciello, Orlando
Abstract: NLRP3 inflammasome is a multiprotein complex that can sense several stimuli such as autophagy dysregulation and increased reactive oxygen species production stimulating inflammation by priming the maturation of proinflammatory cytokines interleukin‐1β and interleukin‐18 in their active form. In the aging brain, these cytokines can mediate the innate immunity response priming microglial activation. Here, we describe the results of immunohistochemical and molecular analysis carried out on bovine brains. Our results support the hypothesis that the age‐related impairment in cellular housekeeping mechanisms and the increased oxidative stress can trigger the inflammatory danger sensor NLRP3. Moreover, according to the recent scientific literature, we demonstrate the presence of an age‐related proinflammatory environment in aged brains consisting in an upregulation of interleukin‐1β, an increased microglial activation and increased NLRP3 expression. Finally, we suggest that bovine may potentially be a pivotal animal model for brain aging studies. Abstract : Autophagy and oxidative stress interact with NLRP3 inflammasome in aged bovine brains.